Can spiral of silence and civility predict click speech on Facebook? - Pang, Natalie (2020)
Opinion expressions on Facebook are characterized by “click speech” in which people express their opinions and support (or disagreement) of posts through the “like,” “comment,” and “share” buttons. This study uses a 2 (low vs. high opinion congruency) x 2 (message civility vs. incivility) between-subject factorial experiment to examine the spiral of silence on participants’ likelihood to interact with social media. We randomly assigned 502 participants to one of four experimental conditions. Results indicate that the fear of isolation increased the likelihood of commenting on Facebook posts and a civil climate increased the likelihood of liking comments on Facebook posts. Findings suggest that “click-speech” could be considered a form of opinion expression.